2013
DOI: 10.1016/j.immuni.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The Satb1 Protein Directs Hematopoietic Stem Cell Differentiation toward Lymphoid Lineages

Abstract: Summary How hematopoietic stem cells (HSCs) produce particular lineages is insufficiently understood. We searched for key factors that direct HSC to lymphopoiesis. Comparing gene expression profiles for HSCs and early lymphoid progenitors revealed that Satb1, a global chromatin regulator, was markedly induced with lymphoid lineage specification. HSCs from Satb1-deficient mice were defective in lymphopoietic activity in culture and failed to reconstitute T lymphopoiesis in wild-type recipients. Furthermore, Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 41 publications
7
94
0
Order By: Relevance
“…SATB1 forms complexes with SWI/SNF factors and positively and negatively regulates the expression of a vast number of genes (28)(29)(30). SATB1 expression is observed in hematopoietic stem cells (HSCs), and its expression is abundant in thymocytes (31,32). Accordingly, SATB1 and its target genes are involved in various cellular functions in different types of blood cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SATB1 forms complexes with SWI/SNF factors and positively and negatively regulates the expression of a vast number of genes (28)(29)(30). SATB1 expression is observed in hematopoietic stem cells (HSCs), and its expression is abundant in thymocytes (31,32). Accordingly, SATB1 and its target genes are involved in various cellular functions in different types of blood cells.…”
mentioning
confidence: 99%
“…For example, it has been demonstrated that SATB1 is necessary for the self-renewal of HSC (32). SATB1 also plays a role in lymphoid lineage specification and/or commitment (31). In SATB1 null mice, however, a dramatic change in cell phenotype is observed in the thymus, where T cell development is mostly stagnated at the DP stage (30).…”
mentioning
confidence: 99%
“…However, so far, no cases of obvious cell fate conversion have been reported in mice with genetically modified polycomb components. This is also true for other epigenetic modulators, such as DNA methyltransferase (Trowbridge et al 2009;Challen et al 2014) or AT-rich sequence binding 1 (Satb1) (Satoh et al 2013;Will et al 2013).…”
mentioning
confidence: 97%
“…Until recently, the majority of reports on SATB1 and SATB2 were limited to roles in development of the immune and nervous systems, respectively, 22,23 and roles for SATB proteins in cancer had not been well described. Han et al 6 demonstrated that SATB1 is highly expressed in aggressive breast tumors and reprograms gene expression to promote growth and metastases.…”
Section: Discussionmentioning
confidence: 99%